Production and immobilization pectinase from Bacillus sp. 2P11 using alginate beads - ANGGRAINI PUTRI UTAMI; FAHRURROZI FAHRURROZI; ANJA MERYANDINI (Society for Indonesian Biodiversity, 2022)
Abstract. Utami AP, Fahrurrozi, Meryandini A. 2022. Production and immobilization pectinase from Bacillus sp. 2P11 using alginate beads. Biodiversitas 23: 3960-3966. Pectinase is one of the enzymes often used in the industrial sector, especially in the food industry, such as extracting and clarifying juices. Previous studies have obtained pectinolytic microbial cultures of Bacillus sp. 2P11 isolated from cocoa beans. Pectinase production using pure pectin substrates such as citrus pectin or pectin from apples costs a lot because these pectins are expensive. Liquid substrate from cocoa pods TSH 858 and ICS 60 with a concentration of 10% is a good amount for pectinase production, and the percentage of total pectin from cocoa pods is 0.823%. The amount of activity of crude extract of pectinase enzyme is 416,780 mU/mL. Precipitation with ammonium sulfate and dialysis increased pectinase activity by 452,335 mU/mL and 586.88 mU/mL, respectively. Enzymes can be used repeatedly with enzyme immobilization. In this study, the immobilization of the enzyme entrapment method with sodium alginate and CaCl2 was designed with the response surface method. The optimum concentration of sodium alginate was 0.5% and 0.3 M CaCl2, with the percentage of an immobilized enzyme at 40.782%. Stability and repeated use of immobilized pectinase can be done up to 5 times.